Analysis on Android-Based Waste Management Evaluation: Toward Efficiency and Sustainability - Siti Nurhayati (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The rapid development of information and communication technology is widely utilized by numerous private sector and governmental entities to enhance services and foster innovations aimed at establishing an accessible, effective, and efficient service system. In addressing the waste issue, the Government of Banyumas Regency is dedicated to innovating for the sake of achieving effective and efficient waste management through the application of digital technology. The examples encompass the utilization of the Salinmas and Jeknyong applications. The innovation in Android application-based waste management aims for public accessibility but encounters certain implementation challenges. This research aims to offer an insight into mobile-based waste management services and to identify the factors, both supportive and inhibiting, in the implementation of Android-based waste management through a Penta Helix approach. The research employed a descriptive method and qualitative approach. Descriptive analysis of the service coverage of Android-based waste management utilized a spatial overlay analysis. Qualitative analysis adopted a thematic approach to identify the supportive and inhibiting factors in the implementation of Android-based waste management through the Penta Helix approach. The research findings indicate that Android-based waste management services are predominantly utilized by urban communities, while rural areas have limited access to Android application services. The analysis of supportive and inhibiting factors in the implementation of Android-based waste management, using the Penta Helix approach, underscores that significance of collaborative synergy and active involvement of all stakeholders, including the public, private, and local communities, in conceptualization and planning processes. Integration of technical, environmental, social, financial, institutional, and political aspects is imperative to ensure the system’s sustainability. The strategic considerations that can be suggested as a solution for Android-based waste management in Banyumas Regency encompass technology, educational aspects, economic factors, institutional framework, policies, collaborative efforts, active participation, and coordination.